Jesus Cristo : o mito do herói salvador na obra Bíblia em ação: de Sérgio Cariello - Ferreira, Cristiano (2017)
This is a research on the convergences of comics, images and myths that appear in the biblical comic narrative in the work of the artist Sérgio Cariello. The question to be answered is: how does Jesus Christ, in the work of this author, fulfill the phases of the myth of the Hero-Savior in the comics? According to Carl Gustav Jung and Joseph Campbell, the myth is presented as a continuous presence in the history of the culture of humanity. When studying the myth, it is not intended to demean and defend the religious creed, since the mythological explanation, from analytical psychology, shows the meaning in the continuity of collective behavior having as its driving force the collective unconscious. Jesus Christ, as a man and as a myth inherited in the social mentality, must be seen also in his humanity, and here in his influence and importance in the culture of humanity. Finally, an attempt is made to establish an application and gauge the space that the use of comics has been occupying in the education and in the influence of the religious culture. It turns out that the heroic characters of comics are present in the Christian churches in their pastors' performance. On the other hand, the work of Sérgio Cariello demonstrates how sufficient is the unique image of Jesus Christ as Savior, and this, in theology, falls within the general revelation.